Textile characteristics of fiber from Huacaya alpacas (Vicugna pacos) - Paucar-Chanca, Rufino (2019)
Fiber from alpacas represents a substantial component of economic output for South American countries. In this study it determined the textile characteristics of fibers obtained from Huacaya alpacas raised at the South American Camelids Research and Development Center-Lachocc (CRDC-Lachocc) located at The National University of Huancavelica (UNH). Fleece samples were obtained from the mid-side rib area of 74 white alpacas (42 females and 32 males) of varying ages. The Average Fiber Diameter (AFD), Standard Deviation of the Average Fiber Diameter (SDAFD), Fiber Diameter Coefficient of Variation (FDCV), Comfort Factor (CF) and Staple Length (SL) were measured as textile characteristics and related to sex and age group. Most of the fleece samples could be classified as baby alpaca fleece according to the Peruvian Technical Standard classification (231.301.2014). Sex had no influence on any textile characteristic (p > 0.05). Meanwhile, age affected only AFD and CF (p < 0.05). Together the results indicated that alpacas farmed at CRDC-Lachocc had good potential to produce high quality fibers.